Effects of N/Ti Atomic Ratio on Microstructure and Properties of TiN Films - PENG Li - jing, ZHANG Jun, XU Chen - ning, WANG Xiao - yang, WANG Mei - han (Cailiao Baohu, 2021)
TiN hard films are the basis of many existing multi - component nitride hard films. The N/Ti atomic ratio has important influences on TiN hard films. Based on the preparation process methods of TiN hard films, the influencing factors and control ways of the change of N content in the films were discussed. Besides, the influences of N/Ti atomic ratio on the phase composition, hardness, wear and abrasion resistance and the photoelectric properties of TiN films were analyzed in detail.